2011
DOI: 10.1007/s11431-011-4543-5
|View full text |Cite
|
Sign up to set email alerts
|

Across-wind loads and effects of super-tall buildings and structures

Abstract: Across-wind loads and effects have become increasingly important factors in the structural design of super-tall buildings and structures with increasing height. Across-wind loads and effects of tall buildings and structures are believed to be excited by inflow turbulence, wake, and inflow-structure interaction, which are very complicated. Although researchers have been focusing on the problem for over 30 years, the database of across-wind loads and effects and the computation methods of equivalent static wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Substituting f = 0.032 Hz, B = 42.9 m and V ¼ 12:96 m=s into the above equation, the corresponding Strouhal number was 0.1059. As suggested by Holmes (2007), the Strouhal number for a squaresection cylinder in uniform turbulent flow is about 0.12, and on the other hand, some wind tunnel test results indicated that the Strouhal number for a square-section cylinder in boundary layer is about 0.1 (Gu et al, 2011), which is close to the identified value in this paper. It was noteworthy that some field measurement studies on Strouhal number for super-tall buildings in turbulent flow were usually based on the Fourier spectrum analysis of wind pressure recorded by pressure transducers (Fu et al, 2012).…”
Section: Velocities and Displacements Deduced From Acceleration Datasupporting
confidence: 88%
See 2 more Smart Citations
“…Substituting f = 0.032 Hz, B = 42.9 m and V ¼ 12:96 m=s into the above equation, the corresponding Strouhal number was 0.1059. As suggested by Holmes (2007), the Strouhal number for a squaresection cylinder in uniform turbulent flow is about 0.12, and on the other hand, some wind tunnel test results indicated that the Strouhal number for a square-section cylinder in boundary layer is about 0.1 (Gu et al, 2011), which is close to the identified value in this paper. It was noteworthy that some field measurement studies on Strouhal number for super-tall buildings in turbulent flow were usually based on the Fourier spectrum analysis of wind pressure recorded by pressure transducers (Fu et al, 2012).…”
Section: Velocities and Displacements Deduced From Acceleration Datasupporting
confidence: 88%
“…In the field of wind tunnel tests, the high frequency force balance technique is widely adopted to measure the overturning forces and bending moments of a super-tall building by a rigid and very slight model attached with force balance measurements at its base (Irwin, 2009;Lam and Li, 2009;Cluni et al, 2011;Gu and Quan, 2011). It is easy to implement and obtain the accurate results in terms of base forces and overturning moments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ensure the service life and security of constructional works, it is necessary to monitor the constructional work systematically during its building and operating. Due to the diversity, complexity and non-deterministic characters of inducing factors of the building subsidence deformation, the mechanical behavior and deformation trend of building subsidence also reflect non-linear characteristics with the coexistence of the uncertainty and randomness [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Existing methods for building subsidence deformation prediction usually establish the time series analysis model by utilizing monitored data [35][36][37][38][39][40].…”
mentioning
confidence: 99%
“…The buildings with configurations other than those stated in the guidelines require wind tunnel tests to determine the wind response. Boundary layer wind tunnel tests have been performed by Lin et al, Gu and Quan, Yang et al, and Amin et al to approximate the responses of tall buildings in terms of pressure coefficient and pressure distribution on the structure due to wind load for different configurations.…”
Section: Introductionmentioning
confidence: 99%